O combate ao racismo nos estádios de futebol brasileiros: análise crítica da legislação e das soluções propostas - SOARES, Pedro Lucas Castro (2024)
Discriminatory acts are not restricted to a specific period of time or to a specific public. On the contrary, they manifest themselves in forms, places and social classes. Speaking specifically of racism, as a complex phenomenon, in many segments of society its confrontation was not immediate, with racist actions being confronted was not immediate, with racist actions being propagated all the time. In this this article, the context of soccer stadiums is chosen to discuss the discriminatory practices discriminatory practices present there, as well as which legal, extralegal and legal and legal instruments are being used to confront these occurrences. Through through a bibliographic review methodology, which studies authors and the normative structure of sports law, the aim is to identify what gaps exist in the the Brazilian legal system.